THE TRANSLATION STRATEGIES OF METAPHOR IN THE MAGIC OF THINKING BIG TRANSLATED INTO BAHASA INDONESIA BY DIAN PARAMESTI BAHAR - Khairani Hayat Situmorang; I Wy. Dirgeyasa; Zanuddin Zainuddin (Universitas Negeri Medan, 2019)
The research dealt with Metaphor Sentences. The aims of this study were: (1) to find out the translation strategies of metaphors are used in The Magic of Thinking Big and (2) to describe the translation strategies maintain metaphors in The Magic of Thinking Big. The research was conducted by using qualitative design. The data of this study were sentences. The data were collected through documentary technique and the instrument was the documentary sheet. The technique of data analysis was descriptive. The finding of this study revealed that: (1) The metaphor in The magic of Thinking Big were translated by applying six translation strategies, namely: word for word Translation (5.3%) lieral translation (4.3%), faithful translation (57.5%), Free translation (3.2%), communicative translation (30.5%) and discursive creation was found (2.2%). (2) The metaphors are maintained that found in the Magic of Thinking Big are original metaphors turned into another original metaphors, stock metaphors turned into another stock metaphors, adapted metaphors turned into adapted metaphors, dead metaphors turned into dead metaphors, original metaphor turned into stock metaphor, stock metaphor turned into original metaphor, meanwhile, 10 original metaphors and 1 dead metaphor are no longer classified as metaphors. Language has special characteristic that is metaphor sentences, therefore in the case of translating of metaphor sentences in which their concept in unknown for readers, the translator often faces the problems to find out the translation strategies to translate metaphor in a source language (SL) and how the metaphor sentences are maintained in the target language (TL).Keywords : Metaphor, Translation Strategies, Maintain Metaphor